Inherited Interleukin 2–Inducible T-Cell (ITK) Kinase Deficiency in Siblings With Epidermodysplasia Verruciformis and Hodgkin Lymphoma. (19th February 2019) - Youssefian, Leila; Vahidnezhad, Hassan; Yousefi, Mehdi; Saeidian, Amir Hossein; Azizpour, Arghavan; Touati, Andrew; Nikbakht, Neda; Hesari, Kambiz Kamyab-; Adib-Sereshki, Mohammad Mahdi; Zeinali, Sirous; Mansoori, Behzad; Jazayeri, Ali; et al.
Abstract: Biallelic mutations in the ITK gene cause a T-cell primary immunodeficiency with Epstein-Barr virus (EBV)–lymphoproliferative disorders. We describe a novel association of a homozygous ITK mutation with β–human papillomavirus (HPV)–positive epidermodysplasia verruciformis. Thus, loss of function in ITK can result in broad dysregulation of T-cell responses to oncogenic viruses, including β-HPV and EBV.